2016
DOI: 10.1097/mop.0000000000000293
|View full text |Cite
|
Sign up to set email alerts
|

Therapies on the horizon for childhood acute lymphoblastic leukemia

Abstract: Purpose of the review The prognosis for children with the most common childhood malignancy, acute lymphoblastic leukemia (ALL) has improved dramatically. However the burden of therapy can be substantial with long term side effects and certain subgroups continue to have a poor outcome. Recent Advances The recent discovery of new genetic alterations in high risk subsets provide targets for precision medicine-based interventions using existing FDA approved agents. Novel immunotherapeutic approaches are being de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…Nevertheless, novel therapies are needed to improve the outcome of patients with Ph-like ALL as this this subtype of ALL represents a disease where precision medicine testing, and treatment approach should be implemented [90,94,99]. Newly discovered genetic alterations that drive HR Ph-like ALL can now be targeted with TKIs and JAK inhibitors leading to clinical trials for this particular HR subset [100]. Birinapant is a small molecule mimetic of the apoptotic regulator SMAC.…”
Section: Page 8 Of 15mentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, novel therapies are needed to improve the outcome of patients with Ph-like ALL as this this subtype of ALL represents a disease where precision medicine testing, and treatment approach should be implemented [90,94,99]. Newly discovered genetic alterations that drive HR Ph-like ALL can now be targeted with TKIs and JAK inhibitors leading to clinical trials for this particular HR subset [100]. Birinapant is a small molecule mimetic of the apoptotic regulator SMAC.…”
Section: Page 8 Of 15mentioning
confidence: 99%
“…Multiple studies have shown that, in addition to allogeneic HSCT, the following novel therapies are effective in patients with drug resistant or relapsed ALL: clofarabine, nelarabine, dasatinib alone or in combination with hyper-CVAD, sphingosomal vincristine, pegylated asparaginase, blinatumomab, ponatinib, chimeric antigen receptor (CAR) T-cells, SRC inhibitor KX2-391 in T-cell ALL and the BCL2 inhibitor venetoclax [54,81,86,100,[120][121][122]. The latter drug has been found to be highly effective in pre-B ALL with MLL-AF4 and TCF3-HLF mutations.…”
Section: Drug Resistance and Relapse In All Patientsmentioning
confidence: 99%
See 3 more Smart Citations